Melasma and Vitiligo in Brown Skin - Handog, Evangeline B.; Enriquez-Macarayo, Maria Juliet (Springer India : Imprint: Springer, 2017)
This book sheds new light on pigmentary disorders in people with brown skin. Brown skin encompasses many races and ethnicities. Due to migration, people with brown skin are seen almost everywhere in the world. A wide variety of pigmentary disorders exists among this population but the most disturbing and challenging are melasma and vitiligo This book covers these two disorders, among people of brown skin, from the epidemiology to management, in a detailed yet easy-to-read and easy-to-use style.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books